Perimetric measurements with flicker-defined form stimulation in comparison with conventional perimetry and retinal nerve fiber measurements - Horn, Folkert; Tornow, Ralf-Peter; Jünemann, Anselm; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2014)
We compared the results of flicker-defined form (FDF) perimetry with standard automated perimetry (SAP) and retinal nerve fiber layer (RNFL) thickness measurements using spectral domain optical coherence tomography (OCT).A total of 64 healthy subjects, 45 ocular hypertensive patients, and 97 "early" open-angle glaucoma (OAG) patients participated in this study. Definition of glaucoma was based exclusively on glaucomatous optic disc appearance. All subjects underwent FDF perimetry, SAP, and peripapillary measurements of the RNFL thickness. The FDF perimetry and SAP were performed at identical test locations (G1 protocol). Exclusion criteria were subjects younger than 34 years, SAP mean defect (SAP MD) > 5 dB, eye diseases other than glaucoma, or nonreliable FDF measurements. The correlations between the perimetric data on one hand and RNFL thicknesses on the other hand were analyzed statistically.The age-corrected sensitivity values and the local results from the controls were used to determine FDF mean defect (FDF MD). The FDF perimetry and SAP showed high concordance in this cohort of experienced patients (MD values, R = -0.69, P < 0.001). Of a total of 42 OAG patients with abnormal SAP MD, 38 also displayed abnormal FDF MD. However, FDF MD was abnormal in 28 of 55 OAG patients with normal SAP MD. The FDF MD was significantly (R = -0.61, P < 0.001) correlated with RNFL thickness with a (nonsignificantly) larger correlation coefficient than conventional SAP MD (R = -0.48, P < 0.001).The FDF perimetry is able to uncover functional changes concurrent with the changes in RNFL thickness. The FDF perimetry may be an efficient functional test to detect early glaucomatous nerve atrophy. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21150